A single serving of mixed spices alters gut microflora composition: a dose–response randomised trial - Wei Wei Thwe Khine (Nature Portfolio, 2021)
Abstract Short-term changes in dietary intake can induce changes in gut microbiome. While various dietary polyphenols have been shown to modulate gut microflora, the acute influence of polyphenol-rich mixed spices has not been explored in a controlled setting. We investigated the effects of a single serving of mixed spices Indian curry consumption, in two separate doses, on the gut microbiome in 15 healthy, Singaporean Chinese males, with age and BMI of 23.5 ± 2.4 years and 22.9 ± 2.2 kg/m2 respectively. We found that a low-polyphenol, no spices Dose 0 Control (D0C) meal led to an increase in Bacteroides and a decrease in Bifidobacterium. In comparison to D0C, there was significant suppression of Bacteroides (p < 0.05) and an increase in Bifidobacterium (p < 0.05) with increasing doses of curry meal Dose 1 Curry (D1C) and Dose 2 Curry (D2C) containing 6 g and 12 g mixed spices respectively. Significant correlations were also found between bacterial changes and plasma phenolic acids. No differences between treatments were observed in the alpha-diversity of the gut microflora. This study has shown that a single serving of mixed spices can significantly modify/restore certain commensal microbes, particularly in people who do not regularly consume these spices.